2020
DOI: 10.1186/s12870-020-02613-y
|View full text |Cite
|
Sign up to set email alerts
|

An RTM-GWAS procedure reveals the QTL alleles and candidate genes for three yield-related traits in upland cotton

Abstract: Background Cotton (Gossypium spp.) fiber yield is one of the key target traits, and improved fiber yield has always been thought of as an important objective in the breeding programs and production. Although some studies had been reported for the understanding of genetic bases for cotton yield-related traits, the detected quantitative trait loci (QTL) for the traits is still very limited. To uncover the whole-genome QTL controlling three yield-related traits in upland cotton (Gossypium hirsutum L.), phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…Different genome-wide association study (GWAS), single locus-GWAS (SL-GWAS), multi-locus GWAS (ML-GWAS), and restricted two-stage, multi-locus, multi-allele GWAS (RTM-GWAS) approaches have been used to search QTNs for LP in a large number of cotton accessions ( Supplementary Table S1 ). For example, using RTM-GWAS, 86 single-nucleotide polymorphism linkage disequilibrium block (SNPLDB) loci for LP were identified from 315 cotton accessions ( Su J et al, 2020 ). A total of 719 upland cotton accessions were screened by GWAS combined with cottonSNP63K array.…”
Section: Qtls Of Cotton Lint Percentagementioning
confidence: 99%
See 2 more Smart Citations
“…Different genome-wide association study (GWAS), single locus-GWAS (SL-GWAS), multi-locus GWAS (ML-GWAS), and restricted two-stage, multi-locus, multi-allele GWAS (RTM-GWAS) approaches have been used to search QTNs for LP in a large number of cotton accessions ( Supplementary Table S1 ). For example, using RTM-GWAS, 86 single-nucleotide polymorphism linkage disequilibrium block (SNPLDB) loci for LP were identified from 315 cotton accessions ( Su J et al, 2020 ). A total of 719 upland cotton accessions were screened by GWAS combined with cottonSNP63K array.…”
Section: Qtls Of Cotton Lint Percentagementioning
confidence: 99%
“…High density SNP maps have been constructed ( Sun et al, 2018 ), including more than 16 association maps ( Supplementary Table S1 ). Many candidate genes for agronomic traits have also been reported ( Fang et al, 2017 ; Huang et al, 2017 ; Sun et al, 2018 ; Shen et al, 2019 ; Su et al, 2019 ; Su J et al, 2020 ; Zhu G et al, 2020 ; Yu et al, 2021 ).…”
Section: Qtls Of Cotton Lint Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…Breeding of resistant varieties is the effective and economic approach to prevent and control VW [ 13 , 14 , 15 ]. To this date, several VW resistance quantitative trait loci (QTLs) have been characterized based on development of high-throughput sequencing and have been shown to contribute to defense responses against VW [ 14 , 16 , 17 ]. In addition, several genes have been identified that contribute to defense responses against VW, including transcription factors, genes involved in plant hormone signaling network and R genes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes affecting crop yield must be identified to reveal the genetic basis and facilitate the increase in crop yield through genetic engineering and hybridization or selective breeding (Gu et al 2020). Genome-wide association study (GWAS) and quantitative trait locus (QTL) analysis are the most efficient methods for detecting yield-related genes in staple crops, such as wheat, maize, rice, and cotton (Alemu et al 2020;Su et al 2020;Wang et al 2020;Zhang et al 2020). However, the yield-related genes of emerging crops are difficult to identify by using GWAS or QTL analysis due to the lack of genomic information.…”
Section: Introductionmentioning
confidence: 99%